(untitled) (Universal International Scientific Journal, 2026)
This article comprehensively explores the importance of emotional intelligence theory and its practical application in the educational process. The article analyzes in detail the methods of developing emotional intelligence, pedagogical strategies, interactive lessons and its role in increasing student motivation. The article also shows how EI can be used in the activities of educators and students.